Nanosilicate-hydrogel microspheres formed by aqueous two-phase separation for sustained release of small molecules - Dharmesh, Ether; Stealey, Samuel; Salazar, Mary Alice; Elbert, Donald; Zustiak, Silviya Petrova (Frontiers in Biomaterials Science, 2023)
Hydrogel microspheres are an attractive option for drug delivery applications due to their ease of injection and potential for tunable controlled delivery. However, their utility is limited due to high initial burst release and rapid overall release, which is especially pronounced for small molecules or small size microspheres. We and others have shown that the addition of two-dimensional nanosilicate (NS) particles to hydrogels can significantly prolong release kinetics from hydrogels while minimizing burst release. Here we explored whether NS could modulate release kinetics of small molecules from small size injectable microspheres. Polyethylene glycol (PEG)-based hydrogel microspheres were fabricated via polymer/salt aqueous two-phase separation (ATPS), which is facile, high yield, and scalable, without the need for organic solvents or oils. Importantly, NS and acridine orange (AO), a model cationic small molecule, were shown to phase separate into the PEG-rich phase, allowing for successful encapsulation within hydrogel microspheres. The fabricated microspheres were stable, similar in size to red blood cells, and easily injectable. The effect of various fabrication parameters, including the addition of NS and AO, on microsphere size and polydispersity were explored. Release of AO was significantly slowed from PEG-NS microspheres compared to PEG-only microspheres and correlated with NS concentration. Two additional small molecules, the chemotherapeutic doxorubicin (positive charge), and the model small molecule Brilliant Blue FCF (negative charge), were shown to exhibit prolonged release, underscoring the broad utility of the system. The dependence of release kinetics on encapsulated NS concentration allows for tunable and prolonged release of small molecules from an injectable hydrogel delivery device.